A comprehensive roadmap for MedTech innovations uptake into the public healthcare system in India - Prakamya Gupta; Charu Rai; Anjaney Shahi; Manisha Sharma; Ranjan Choudhury; Atul Kotwal (Frontiers Media S.A., 2023)
BackgroundThe burden of communicable, non-communicable diseases and reproductive maternal, newborn, child & adolescent health in India, reflects the necessity to develop tailored solutions. The plethora of MedTech innovations has provided healthcare facilities with more effective, affordable and accessible healthcare for people across the country. However, in spite of the Make-in-India scheme in the country, the indigenously developed healthcare technology is far from making an impact on the healthcare system.ObjectiveTo present a roadmap for MedTech innovations for their successful deployment into the public healthcare system.MethodologyIn addition to the literature review, recommendations were included from several stakeholders such as innovators, manufacturers, policymakers, subject matter experts, funding organizations, State health officials etc.Results and conclusionThe journey of healthcare innovation from need identification to ideation, to prototyping and validation has paved the way towards the de novo design that caters to unmet needs. Innovations at the advanced technology readiness level (TRL 7/8 and above) demand a holistic and multidisciplinary approach which includes clinical validation, regulatory approval and Health technology assessment. The deployment of healthcare technology into the public healthcare system must consider resources (e.g., time, staff, budget, investment policies), ethical concerns (privacy, security, regulations, ownership), governance (policy, accountability, responsibility etc.), and Skills (capabilities, culture, etc.). The technologies are considered for field trials before the uptake in the public health system. Technology can be a key tool in achieving Universal Health Coverage but its use has to be strategic, judicious, and cognizant of issues around privacy and patient rights.